A review of the use of portable technologies as observational aids in the classroom. Issue 3 (11th March 2019) - Goh, Felicia; Carroll, Annemaree; Gillies, Robyn M.
Abstract : Purpose: Current classroom observation strategies include questionnaires, interviews, tests, self-report metrics and live or video review observation. However, these traditional methods are subject to biases from observers in determining behavior nuances, as well as being difficult to analyze for rapid and practical feedback. In addition, the invasiveness of extra body equipment in the classroom may alter the dynamic between students and teachers. The emergence of portable devices into mainstream usage has opened a pathway for a relatively novel source of quantitative data, free from observer bias and often with accompanying analytical tools for convenience. The purpose of this study is to summarize current uses of portable technology and explore how such devices could be used as monitoring tools by both schools and education researchers. Design/methodology/approach: Functions based on utility outside the education field are proposed for monitoring student activity, posture and movement, as well as proximity and relationships to others and their environment. Deterrents to device implementation in regular classroom use, such as the importance of considering ethical issues and hardware limitations, are also covered. Findings: While current portable technology is unlikely to replace more commonly used techniques of observing classes, they have the capacity to augment qualitative strategies, particularly in the area of real-time data output. Research limitations/implications: Ideally, the lack of unbiased observational tools available and increased adoption of portable devices in classrooms could prompt future advances in technology for teaching and learning environments. Originality/value: This review summarizes potential uses for portable technology in classroom observation strategies undertaken by researchers and teachers to improve learning and teaching practices.